Pengaruh Personalitas, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru SD Kecamatan Bukit Raya Kota Pekanbaru - Misrina Misrina; Suroyo Suroyo; Sri Tatminingsih (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to determine the components that affect teacher performance in elementary schools in Bukit Raya District, Pekanbaru City. The research variables are personality, work motivation, work environment, and teacher performance. The research uses a quantitative approach. The population was elementary school teachers in Bukit Raya District, Pekanbaru City with a sample of 176 teachers selected by proportional sampling. Data were collected by survey technique using a questionnaire. Data were analyzed using Multiple Regression. The results showed that the variables of personality, work motivation, and work environment had a significant effect on the performance of elementary school teachers in Bukit Raya District, Pekanbaru City. The recommendation that can be submitted is that self-development activities to improve teacher personality, teacher work motivation, and work environment for teachers in elementary schools in Bukit Raya District, Pekanbaru City need to be carried out optimally